2007
DOI: 10.1089/fpd.2006.0069
|View full text |Cite
|
Sign up to set email alerts
|

1% Calcium Chloride Treatment in Combination with Gamma Irradiation Improves Microbial And Physicochemical Properties of Diced Tomatoes

Abstract: The purpose of this study was to determine the effect of a combination of a 1% calcium chloride dip with low dose irradiation on microbial populations, and biochemical and physical properties, of fresh diced tomatoes during a two-week storage period. Vine tomatoes at the light-red stage (trial 1) and Celebrity tomatoes at the table ripe stage (trial 2) were diced, dipped in 1% CaCl(2), and irradiated at 1 kGy from a Co(60) source. Tomatoes were also contaminated with cocktail of nalidixic-acid resistant Salmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…A dose of 2.0 kGy completely controlled the fungal and bacterial counts on carrot slices stored at 5°C for 2 weeks. The effect of a combination of a 1% calcium chloride dip with low-dose irradiation (1.5 kGy) on microbial populations was evaluated on fresh diced tomatoes during a two-week storage period (Prakash et al, 2007). The effect of a combination of a 1% calcium chloride dip with low-dose irradiation (1.5 kGy) on microbial populations was evaluated on fresh diced tomatoes during a two-week storage period (Prakash et al, 2007).…”
Section: F Irradiationmentioning
confidence: 99%
“…A dose of 2.0 kGy completely controlled the fungal and bacterial counts on carrot slices stored at 5°C for 2 weeks. The effect of a combination of a 1% calcium chloride dip with low-dose irradiation (1.5 kGy) on microbial populations was evaluated on fresh diced tomatoes during a two-week storage period (Prakash et al, 2007). The effect of a combination of a 1% calcium chloride dip with low-dose irradiation (1.5 kGy) on microbial populations was evaluated on fresh diced tomatoes during a two-week storage period (Prakash et al, 2007).…”
Section: F Irradiationmentioning
confidence: 99%
“…2004; Schmidt et al . 2006; Prakash et al . 2007) with no change in texture, color or sensory quality (Koorapati et al .…”
Section: Discussionmentioning
confidence: 99%
“…Stem scars were removed and the tomatoes were pureed for 30 s using a laboratory blender (Waring commercial model number S13L31, Torrington, CT). Preliminary studies showed interference of the native flora with the Salmonella inoculum; therefore, the tomato puree was autoclaved prior to inoculation (Prakash et al . 2007).…”
Section: Methodsmentioning
confidence: 99%
“…For powdered dehydrated vegetables higher treatments (3-5 kGy) were suggested (Dong-Ho et al, 2002). Treatments for instance calcium chloride could decrease the effect of irradiation on fruit firmness (Prakash et al, 2007). Also, D10 values for various Salmonella strains in orange juice were between 0.6 and 0.8 KGy (Niemira & Lonczynski, 2006).…”
Section: Fruits and Vegetablesmentioning
confidence: 94%